Virtual worlds and social and educational inclusion: case study at Secondary Education Institute Cal Gravat - Linda Castañeda Quintero; María del Mar Román García; Ramón Barlam Aspasch (Springer, 2015)
This article presents a case study with the goal of becoming familiar with and understanding the incorporation of one virtual learning world -Espurnik- in a curricular diversification classroom with students in a situation of educational exclusion or academic failure. This investigation was carried out from an interpretive paradigm with a qualitative methodology grounded in the Case Studies. The data was collected using different qualitative techniques: documentary analysis, direct observation in the virtual world, semi-structured interview with the teacher, and group interview with the students. The conclusions indicate that the emphasis must not be placed on technologies, but rather on the methodological change that many of them foster, setting up the student not a consumer of information but rather a creator and producer of knowledge in a context of collaborative work, attending comprehensively to the community context of the students' educational development.